Analysis of Excessive Mobile Phone Use on Behavioral Changes and Sleep Patterns of Elementary School Students: A Systematic Literature Review - Yolanda Karamoy; Eny Munisah (Journal for Lesson and Learning Studies, 2026)
Excessive mobile phone use among elementary school students has become a growing concern because it may negatively affect children’s behavioral development and sleep health. Previous studies discussing behavioral changes and sleep disturbances due to gadget use are still fragmented and rarely examined simultaneously within the context of elementary education. This study aims to analyze and synthesize recent scientific evidence regarding the effects of excessive mobile phone use on behavioral changes and sleep patterns among elementary school students. The study employed a Systematic Literature Review (SLR) design using the PRISMA guidelines and the Kitchenham and Charters framework. Literature searching was conducted through Google Scholar, ScienceDirect, SpringerLink, and SINTA databases covering publications from 2020–2025. A total of 10 selected articles involving elementary school students as research subjects were analyzed using thematic synthesis techniques. Data collection was carried out through document analysis using article screening and eligibility instruments based on inclusion and exclusion criteria. The findings indicate that excessive gadget use is associated with decreased learning motivation, impaired concentration, emotional instability, reduced social interaction, and increased behavioral problems. Furthermore, prolonged screen time contributes to shorter sleep duration, poor sleep quality, and irregular sleep patterns. The study concludes that uncontrolled mobile phone use may adversely influence children’s behavioral and sleep development. These findings provide conceptual implications for parents, educators, and policymakers in developing strategies for healthy digital use among elementary school students.